2020
DOI: 10.2196/17060
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Attitudes Toward an Online Patient Portal for Communicating Laboratory Test Results: Real-World Study Using the eHealth Impact Questionnaire

Abstract: Background Communicating laboratory test results online has several advantages for patients, such as improving clinical efficiency and accessibility, thereby helping patients to take an active role in managing their health. Objective This study aimed to investigate the experiences and self-efficacy of patients using an online patient portal that communicates laboratory test results. Methods We used the onlin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…In line with these trends, innovations such as eHealth are required to maintain high quality of care [4][5][6]. eHealth includes a wide range of web-based interventions, for example e-consults, telemonitoring, and web-based viewing of medical records [1,7,8]. However, eHealth is more than a technology; it is another way of working and thinking and requires a change in attitude, which goes beyond the boundaries of a local health care organization [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these trends, innovations such as eHealth are required to maintain high quality of care [4][5][6]. eHealth includes a wide range of web-based interventions, for example e-consults, telemonitoring, and web-based viewing of medical records [1,7,8]. However, eHealth is more than a technology; it is another way of working and thinking and requires a change in attitude, which goes beyond the boundaries of a local health care organization [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Organizations are increasingly working with eHealth; however, implementing eHealth into the regular health care system requires organizations to change the way they work [9][10][11]. eHealth enables patients to have a more active role in managing their health [7,12,13], which affects interactions between the patient and health care professional [14][15][16][17]. Furthermore, working with eHealth technology requires workflow adjustments for health care professionals [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the included studies had a quantitative descriptive design (n=28) [ 12 , 13 , 15 , 25 - 50 ]. In the remaining studies, a (quantitative) nonrandomized design was reported 6 times [ 32 , 51 - 55 ], a randomized controlled design was reported 5 times [ 56 - 60 ], a mixed methods design was reported 3 times [ 14 , 61 , 62 ], and a qualitative design was reported 3 times [ 63 - 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the thematic analyses provided insight into potential reasons why the Confidence and Identification and Understanding and Motivation subscale scores were below the recommended value [ 20 , 21 ]. Lack of personalized information, protocols based on the average patient, no interaction with clinicians, and missing reference data of peers were potential reported explanations.…”
Section: Discussionmentioning
confidence: 99%
“…We transformed the total scores for each subscale to a scale of 0 to 100. A score of 65 or higher was considered as a positive attitude with higher scores representing a more positive attitude toward the app [ 20 , 21 ]. All subscales have good internal consistency, test-retest reliability, and construct validity (Cronbach α=.88-.90) [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%